Discriminating taste : how class anxiety created the American food revolution - Finn, S. Margot, 1981- (Rutgers University Press, 2017)
A provocative look at contemporary food culture, Discriminating Taste critically examines cultural touchstones from Ratatouille to The Biggest Loser, identifying how ""good food"" is conflated with high status. Drawing historical parallels with the Gilded Age, Margot Finn argues that the rise of gourmet, ethnic, diet, and organic foods must be understood in tandem with the ever-widening income inequality gap.